PRIORITY DETERMINATION OF IT PROJECT TASKS BASED ON FUZZY LOGIC - VASYLKIV, NADIIA; DUBCHAK, LESIA; TURCHENKO, IRYNA; MINCHUK, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Making a decision about the possibility of performing individual works on the system creation depends on the quality of the conducted research in the field of computer system use, the formed requirements, proposed solutions and the correct distribution of task performance priorities. The task of business analysts in IT companies is the control over the fact, that the created product fully meets the needs, and requirements of the customer of high quality. At the same time, the business analyst's ability to make decisions about the scope of work and their priority in conditions of uncertainty is important; in particular, whether a sufficient number of tasks are prepared for execution in order to be able to predict the work of the team. The purpose of this work is to prioritize IT project tasks based on user story metrics, including readiness, permission to execute and task complexity. Due to the fact that IT projects, the products of which are computer systems, are often carried out under conditions of uncertainty, it is advisable to use fuzzy logic to determine the priority of tasks. A fuzzy system of prioritization of project work is proposed, which has as input values the state of task readiness, permission for execution and complexity. The output of the developed fuzzy system is the priority of the project tasks. The Fuzzy Logic Toolbox for MATLAB is used to build a fuzzy system. The model of the dependence of output values due to inputs is given by Mamdani's inference mechanism. The membership functions of the input variables are given by a bell shape, and the output variables are triangular. The rule base of the proposed fuzzy system consists of 23 "if-then" rules. The fuzzy system takes into account the states of each indicator and, based on their combinations, determines the priority of the task according to which the business analyst and the IT project manager for the creation of a computer system apply actions to either improve the state of the indicators or distribute high-priority tasks among individual performers. The proposed fuzzy system allows you to simulate the situation regarding the priority of tasks at any stage of the IT project implementation, when it is necessary to clarify the requirements for the computer system or make changes to the project caused by uncertainties, as well as when analyzing the perspective of the workload of the project team. The business analyst's correct prioritization of tasks using a fuzzy system and it will contribute to the successful implementation of projects and the confidence of project team members in the prospect of employment.
Keywords: IT project; computer system; task priority; fuzzy logic; fuzzy system